Disaster Mitigation Tactics Through Enhanced Higher Order Thinking Skills via Active Learning in Social Science Education - Mulianingsih, Ferani; Suharini, Erni; Handoyo, Eko; Purnomo, Arif (Journal of Ecohumanism, 2025)
This article aims to discuss innovative educational strategies to enhance students’ understanding and engagement in disaster mitigation through social science learning. The approach used emphasizes the utilization of active learning to strengthen Higher Order Thinking Skills (HOTS) in facing complex disaster challenges. Through field experiences and literature studies, this article outlines the effectiveness of Active Learning in providing in-depth understanding of disaster mitigation. Additionally, it discusses the application of group discussions, role-playing games, and collaborative projects in fostering students’ critical, analytical, and creative thinking. Through this approach, it is hoped that students will gain theoretical knowledge about disasters and practical skills to effectively address real-world challenges. The practical implications of this article lie in curriculum development and social science teacher training. In conclusion, the integration of Active Learning in social science education can be a strategic step in preparing future generations to manage disaster mitigation effectively.